Tolerance to in-band crosstalk of virtual carrier-assisted direct detection multi-band OFDM system - Pinheiro, B. R. (2022)
The tolerance to in-band crosstalk of virtual carrier (VC)-assisted direct detection (DD) multi-band orthogonal frequency division multiplexing (MB-OFDM) system is assessed numerically through Monte-Carlo simulation and considering a single interferer. The influence of the virtual carrier-to-band power ratio (VBPR) and the virtual carrier-to-band gap (VBG) of the interferer on the in-band tolerance is also studied. We show that, for interferers with the same VBG as the selected signal, the increase of the VBPR of the interferer leads to lower optical signal-to-noise ratio (OSNR) penalties. The increase of the VBG of the interferer with central frequency different from the selected signal also leads to lower OSNR penalties. When the central frequencies of the interferer and selected bands are the same, the variation VBG of the interferer can lead to 11 dB less tolerance to in-band crosstalk of the VC-assisted DD OFDM system.